Incidence of Clostridium difficile infection in patients receiving high-risk antibiotics with or without a proton pump inhibitor. Issue 2 (February 2016) - Gordon, D.; Young, L.R.; Reddy, S.; Bergman, C.; Young, J.D.
Summary: Background: Considering the incidence and severity of Clostridium difficile infection (CDI), risk reduction strategies are crucial. Prior studies suggest that proton pump inhibitor (PPI) use can increase the risk of CDI over antibiotics alone; however, data and guidelines have been conflicting. Aim: The aim was to compare CDI incidence in patients receiving high-risk antibiotics, comparing rates in those prescribed a PPI versus those without overlapping PPI exposure. Methods: This retrospective cohort study assessed the incidence of CDI in veterans receiving high-risk antibiotics over an approximately three-year period. High-risk antibiotics were defined as: ciprofloxacin, levofloxacin, moxifloxacin, clindamycin, ceftriaxone, cefotaxime, ceftazidime, or cefixime. Findings: We identified subjects who were prescribed any high-risk antibiotic, finding 3513 on a concomitant PPI and 6149 not taking a PPI. Of these subjects, 111 were diagnosed with CDI and met inclusion criteria. Baseline characteristics, CDI severity, length of hospitalization and antibiotic therapy prior to infection were similar in both groups. The incidence of CDI was significantly higher in patients prescribed a PPI (odds ratio: 2.2; 95% confidence interval: 1.52–3.23; P  = 0.0001). A strong association was found between concurrent PPI use with fluoroquinolones ( P  = 0.005) and clindamycin ( P  = 0.045). Conclusion: The use of PPIs together with high-risk antibiotics was associated with a significantly higher incidence of CDI. Our study provides further support for the CDI prevention strategy of judicious PPI use, especially in patients receiving high-risk antibiotics. Prudent avoidance of PPIs may reduce the incidence of CDI, a major cause of morbidity and mortality worldwide.